The evaluation of carrier material for increasing qualities of gel inoculum for nata de coco - RUTH MELLIAWATI (Society for Indonesian Biodiversity, 2008)
Producion of nata de coco is growing fast, in line with increasing product of biocellulose demand. It is requrire a pure inoculum to reach the best biocellulose product. The aim of this reseach is to evaluate the most appropriate carrier material of gel inoculum for nata de coco. The four carrier material are Carboxy Methyl Cellulose (CMC), Agar, Sagu starch and biocellulose pap and its inoculated by Acetobacter sp. RMG-2 and A. xylinum. After inoculation, then put in the plastic bag (50 g/bag) and stored in 4Â° C. The texture of gel, population of cell andbiocellulose production were observer in 7 days. The result shown that all matterial were suitable to used as carrier for gel inoculum. Both CMC and biocellulose pap have good texture as standard qualities. Population of A. xylinum was 1.28x109 cfu/mL (in CMC carrier), 1.6x106 cfu/mL (in biocellulose pap carrier) after 15 weeks. The weight of biocellulose production was 500 g/L and 740 g/L medium respectively. While the population of Acetobacter sp. RMG-2 on CMC carrier was 1.79x108 cfu/mL and 7.75x107 cfu/mL on cellulose carrier with the weight of biocellulose production 630 g/L and 775 g/L medium respectively. Thus, the carrier material (CMC and Biocellulose pap) are able to keep bacteria without loss their capability to produce cellulose.Key words: Acetobacter sp. RMG-2, Acetobacter xylinum, carrier material, gel inoculum, nata de coco.